Impact of halo-pelvic traction duration on pulmonary improvement quantified by pulmonary function tests and three-dimensional lung reconstruction in severe rigid kyphoscoliosis: a prospective cohort study - Lijin Zhou; Yihan Yang; Honghao Yang; Jianqiang Wang; Zhangfu Li; Duan Sun; Yiqi Zhang; Yunsheng Wang; Yong Hai (Journal of Orthopaedic Surgery and Research)
Abstract Background Severe and rigid kyphoscoliosis, characterized by extreme spinal curvature > 100° and limited flexibility < 30%, significantly impacts pulmonary function. While halo-pelvic traction (HPT) is an established method for improving lung function in patients with scoliosis, the optimal duration of treatment remains undefined. Methods This study included 64 patients who underwent HPT before posterior spinal fusion surgery. Patients were divided into short-term traction group (2 months < traction duration ≤ 4 months), the middle-term traction group (4 months < traction duration ≤ 6 months), and the long-term traction group (traction duration > 6 months). Pulmonary function tests (PFTs) were performed in all patients. Using three-dimensional (3D) lung reconstruction from computed tomography, changes in lung volume were analyzed. The statistical analyses were conducted using SPSS (version 26.0; IBM) and GraphPad Prism (version 10.1.2). Results Among 64 patients, total lung capacity (TLC) increased significantly in the middle‑term traction (2.62 ± 0.89 L to 3.10 ± 0.85 L) and long‑term traction (2.39 ± 0.98 L to 2.98 ± 0.80 L) groups. Total lung volume (TLV) improved significantly in the short‑term (1.81 ± 0.50 L to 2.13 ± 0.44 L), middle‑term (2.62 ± 0.89 L to 3.10 ± 0.85 L), and long‑term (2.39 ± 0.98 L to 2.98 ± 0.80 L) traction groups. Concave-side lung volume also increased significantly in three groups. Middle-term HPT exhibited greater TLV and concave-side lung volume change rate improvement than the short-term group, while long-term HPT showed no additional advantage over middle-term treatment. HPT also significantly improved T1-T12 distance, thoracic kyphosis, and main Cobb angle. Conclusions HPT is an effective treatment for severe and rigid kyphoscoliosis, and 4 to 6 months may be the optimal HPT duration to improve pulmonary function.